Pelaksanaan Layanan Bimbingan Dan Konseling Di Sekolah Dasar - Dea Mustika; Anggarda Paramita Muji; Mega Iswari (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
In elementary schools the implementation of guidance and counseling services is carried out by the classroom teacher. But in fact, there are still classroom teachers who do not understand about the counseling services and guidance that must be applied. This research aims to describe the implementation of guidance and counseling services in elementary schools. This research is a qualitative descriptive study with data sources involving classroom teachers and principals. Data collection techniques include interviews, observations and documentation. The conclusion of the research results that the class teacher has tried to carry out guidance and counseling activities even though the services provided cannot be said to be maximal. Further efforts are needed to increase teacher understanding by conducting training, holding meetings or maximizing discussions on teacher working group forums.